All the Bright Places: Rasch Analysis of PERMA (Positive Emotion, Engagement, Relationship, Meaning, and Accomplishment) Model on Students - Sumi Lestari; Intan Rahmawat; Khoirul Anam (Program Studi Psikologi, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Mulawarman, 2026)
Well-being in the concept of positive psychology is referred to as flourishing or PERMA, which consists of five pillars: Positive Emotion, Engagement, Relationship/Positive, Meaning, and Accomplishment/Achievement. By possessing these five pillars of PERMA, individuals tend to live a happier, more meaningful, and more beneficial life, develop positive relationships with others, and cultivate a positive mindset that fosters positive emotions while reducing negative ones. As a result, individuals are more likely to feel satisfied, happy, and able to live their lives to the fullest. This study aims to obtain a fit model between Positive Emotion, Engagement, Relationship/Positive, Meaning, and Accomplishment/Achievement and to examine the correlations among the PERMA constructs. The research employed a quantitative method by conducting model testing using Structural Equation Modeling (SEM). The subjects were 325 male and female university students. The measurement instruments used in this study were the Dispositional Positive Emotion Scale (DPES) to measure positive emotions, the Meaning in Life Questionnaire (MLQ) to measure meaning in life, the Life Engagement Test (LET) to assess engagement, the Positive Relationship Questionnaire (PRQ) to measure positive relationships, and the Achievement Goal Questionnaire Revised (AGQR) to measure the achievement construct. The results indicate that the PERMA model (positive emotion with engagement, meaning, and accomplishment) fits, meaning that the modified model shows no differences between the model and the data. Thus, the theorized model fits the research data. These findings show that increasing mental health literacy plays an important role in encouraging healthy behavior and strengthening family resilience. Therefore, the implications of this study can serve as a foundation for developing more targeted educational programs and public policies to build healthy and resilient families.